Problems of Language Acquisition from a Psycholinguistic Perspective - Anam, Choirul; Firmansyah, Muhamad Taufiq (Tarsib: Jurnal Program Studi PGMI, 2024)
Language acquisition theory (LAT) is developing very rapidly. There are hundreds, even thousands of language assessment theories, but the ones that often appear in language study literature are twenty-four which are summarized in four groups, namely Behaviorist, Cognitive, Nativist, and Huanistic. The LAT Operant Conditioning Model is one of the behaviorist groups proposed and developed by B.F. Skinner, a very famous behaviorist psychologist in his time. Many new LATs have emerged that strengthen and weaken previous LATs, but do not mean eliminating or destroying them. Most new LATs criticize or weaken previous LATs. The Nativist Language Acquisition Device (LAD) of LAT Model is strongly supported by transformational generative linguistics and Descartes’ rationalist philosophy which believes that language is a reflection of human thought and intelligence and is always reproduced by individuals with operations that underlie the range of human desires and consciousness. Language is considered as something created by the dynamism and abilities of the human organism that focuses on its creative abilities. The Creative Construction Model of LAT emerged almost simultaneously with the Monitor Model of LAT.